The Effectiveness of Using Kagan Strategies in Eight Grad Students Achievement and the Development of their attitudes towards Science Education - shehada, fawaz (Advances in Social Sciences Research Journal, 2018)
The purpose of this study is to gain insight into the effectiveness of using of Kagan's strategies for eighth grade students achievement and to develop their attitudes toward science. To achieve this goal, the study utilized an achievement test to measure the students' attitudes toward science, a measure of attitudes towards science which is prepared by the researcher and the teacher's guide uses Kagan strategies. The validity of the instrument of the study has confirmed. The number of study size (56) students and were divided into two groups: experimental group with (28) students and controlled group with (28) students also, the experimental group will be taught through the training program and the controlled group will be taught in the traditional way. The study resulted on an existence of a statistical significance in the applications of the pre- and post-tests of the achievement, there were also statistical differences in the two applications of the pre and posttests of the science trends measure, and for the favor of the post application. The study recommends that Training teachers on modern trends in teaching including strategies and design classrooms that allow teaching according to the modern teaching methods that require those designs.